Pelatihan Pengelolaan Adiministrasi Koperasi Jasa Bakti Mandiri Jaya di Kampung Juang An-Nahdliyah Kelurahan Sodong Basari - Arlinda Ayu Diah Arfani; Pubita Sasti Fintani; Wida Anggriani (Syntax Corporation Indonesia, 2025)
This research aims to improve the administrative management of the Cooperative in Kampung Juang An-Nahdliyah, Sodong Basari Village. The establishment of Kampung Juang An-Nahdliyah as the Village of Agrarian Reform Awakening in 2023. The village is expected to improve the economic welfare of its residents through a cooperative named Koperasi Jasa Bakti Mandiri Jaya. However, the administration management is still considered lacking, which is caused by the low quality of human resources. This research recommends cooperative administration training as a means to improve administrative performance, such as the procedures for creating and implementing the 16 mandatory cooperative books. This research shows that administrative training is an effective solution to improve the understanding of cooperative administration in Kampung Juang An-Nahdliyah.